2007
DOI: 10.1152/ajpheart.00670.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ signaling in mouse mesenteric small arteries: myogenic tone and adrenergic vasoconstriction

Abstract: Zacharia J, Zhang J, Wier WG. Ca 2ϩ signaling in mouse mesenteric small arteries: myogenic tone and adrenergic vasoconstriction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 36 publications
(25 reference statements)
2
29
1
Order By: Relevance
“…Ca 2ϩ puffs arise from the synchronous opening of ϳ30 IP 3 R channels distributed within a ϳ400-nm diameter cluster in Xenopus oocytes (170,194 (10,18,29,111,190). In isolated retinal arteriole SMCs, ET-1 increased Ca 2ϩ oscillation frequency and this elevation was inhibited by blockers of IP 3 Rs and RyRs, indicating that IP 3 R-RyR cross talk stimulates Ca 2ϩ oscillations (190,218 (249). Similarly, ANG II receptor antagonists abolished Ca 2ϩ ripples and reduced myogenic tone in tail arteries (9).…”
Section: Cellular Regulators Of Smc Ip 3 R Activitymentioning
confidence: 99%
See 2 more Smart Citations
“…Ca 2ϩ puffs arise from the synchronous opening of ϳ30 IP 3 R channels distributed within a ϳ400-nm diameter cluster in Xenopus oocytes (170,194 (10,18,29,111,190). In isolated retinal arteriole SMCs, ET-1 increased Ca 2ϩ oscillation frequency and this elevation was inhibited by blockers of IP 3 Rs and RyRs, indicating that IP 3 R-RyR cross talk stimulates Ca 2ϩ oscillations (190,218 (249). Similarly, ANG II receptor antagonists abolished Ca 2ϩ ripples and reduced myogenic tone in tail arteries (9).…”
Section: Cellular Regulators Of Smc Ip 3 R Activitymentioning
confidence: 99%
“…It was concluded that ANG II produced locally within the arterial wall stimulates Ca 2ϩ ripples, which regulate myogenic tone (9). Therefore, IP 3 Rmediated Ca 2ϩ ripples may be a Ca 2ϩ signal by which the local renin-angiotensin system in the arterial wall contributes to myogenic constriction (9,249 sparks, albeit in a small number of SMC types (116,190,218,252). RyR-and IP 3 R-mediated SR Ca 2ϩ release both stimulated Ca 2ϩ sparks in SMCs of choroidal and retinal arterioles, pulmonary artery, and trachea (116,190,218,252).…”
Section: Cellular Regulators Of Smc Ip 3 R Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of the spatial and temporal patterns of the changes in [Ca 2+ ] i are of fundamental importance in determining their efficacy in activating contraction, through Ca 2+ /calmodulin-dependent myosin light chain kinase. Confocal imaging of [Ca 2+ ] i within single smooth muscle cells in the arterial wall has shown that the spatiotemporal patterns of the agonist-stimulated Ca 2+ response are more complex than previously thought, as in many types of blood vessels activation of α 1 -adrenoceptors elicits propagating Ca 2+ waves that occur asynchronously in the individual smooth muscle cells [2,3,4,5,6,7]. Increasing concentrations of agonist are associated with graded contraction and recruitment of cells which produce asynchronous Ca 2+ waves of increasing frequency [5,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…6 However, pressure elevation also evokes asynchronous Ca 2 þ waves within individual vascular smooth muscle cells because of release of Ca 2 þ from the sarcoplasmic reticulum, 42,43 similarly to the Ca 2 þ waves observed during agonist-induced contraction. 44 Thus, myogenic constriction is suppressed by membrane hyperpolarization, block of voltagegated Ca 2 þ channels, removal of extracellular Ca 2 þ , or application of ML-7 (which inhibits MLCK activity). 2,6,43,45,46 The extent of myogenic depolarization must be precisely controlled to obtain an appropriate increase in [ 6,42 However, these changes are not sufficient to explain the phenomenon.…”
Section: The Mechanosensormentioning
confidence: 99%